SOCIAL NETWORK-BASED EMPOWERMENT IN THE DIGITAL ERA A STUDY IN THE UMKM NAIK KELAS COMMUNITY - Imam Mahmud; Erna Rochana; Usman Raidar; Teuku Fahmi; Azis Ahmad (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Writing a Challenges in the business management process with the adoption of the use of digital technology, and limited social networks are still the main obstacles in the process of empowering MSMEs in each region. This research was conducted to analyse the contribution of social networks in the digital era to the empowerment of MSMEs. The research aims to map the forms of social networks that contribute to the empowerment process of each member who is a member of the community, especially in identifying various forms of digital innovation that have been successfully carried out by MSME actors and also clarifying the factors that encourage and hinder their implementation. The research was conducted using a descriptive qualitative approach through interviews, observation, and documentation. The results showed that social networking in the digital era in several social media groups created by the community provides unlimited space in providing business management processes including business licensing run by MSMEs in Lampung.